2019
DOI: 10.1089/lgbt.2018.0149
|View full text |Cite
|
Sign up to set email alerts
|

Latent Classes of Polysubstance Use Among Adolescents in the United States: Intersections of Sexual Identity with Sex, Age, and Race/Ethnicity

Abstract: Purpose: We aimed to estimate latent classes of concurrent polysubstance use and test for sexual orientation differences in latent class memberships with representative data from adolescents living in 19 U.S. states. We also tested whether sex, race/ethnicity, and age moderated the sexual identity differences in polysubstance use class memberships. Methods: We analyzed data from 119,437 adolescents from 19 states who participated in the 2015 Youth Risk Behavior Survey. Latent class analysis characterized polys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 40 publications
3
8
0
Order By: Relevance
“…We found that compared to their heterosexual counterparts, SM young adult smokers had significantly increased odds of engaging in same-day use of both cigarettes and cannabis as well as same-day use of all three substances. This finding is consistent with the extant literature showing greater odds of multiple substance use among SM adolescents and young adults than their heterosexual counterparts; however, those studies focused on any co-use occurring within a large timeframe of 30 days or 1 year (Coulter et al, 2019;Dermody, 2018;Dermody et al, 2016;Kecojevic et al, 2017). Furthermore, SM participants in our study reported fewer days with single substance use and more days with multiple substance use than their heterosexual peers.…”
Section: Discussionsupporting
confidence: 91%
“…We found that compared to their heterosexual counterparts, SM young adult smokers had significantly increased odds of engaging in same-day use of both cigarettes and cannabis as well as same-day use of all three substances. This finding is consistent with the extant literature showing greater odds of multiple substance use among SM adolescents and young adults than their heterosexual counterparts; however, those studies focused on any co-use occurring within a large timeframe of 30 days or 1 year (Coulter et al, 2019;Dermody, 2018;Dermody et al, 2016;Kecojevic et al, 2017). Furthermore, SM participants in our study reported fewer days with single substance use and more days with multiple substance use than their heterosexual peers.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with prior work that found higher risks and levels of polysubstance use among White adolescents and adolescents whose parents of other family members have substance use problems (Gilbert et al, 2020;Russell et al, 2015;Tomczyk et al, 2016). For example, a recent study found that White youth were more likely than Black youth to be tobaccoalcohol users, medium-frequency three-substance users, and high-frequency three-substance users compared with nonusers (Coulter et al, 2019). In contrast to these risk factors, we found that high quality mother-child relationships predicted a lower initial number of substances used.…”
Section: Discussionsupporting
confidence: 90%
“…6 Our study findings differed from that review in two main ways. First, we identified only one multi-use group, while other studies have identified a moderate and a high multi-use group; 14,24,[59][60][61][62] although many of these surveys included additional illicit substances (i.e. ecstasy, amphetamines, cocaine 14,24,59 ), which were not examined in this study.…”
Section: Discussionmentioning
confidence: 99%